A catalogue of Indian species of the genus Frisilia Walker (Lepidoptera: Lecithoceridae), with descriptions of two new species from India and South East Asia. (2nd January 2019) - Park, Kyu-Tek; Shashank, P. R.
Abstract: A catalogue of the Indian species of the genus Frisilia Walker is provided, with eight previously known and one new species, F. chandrai sp. nov. described from India. In addition, the other new species, F. yangbaei sp. nov. described from Cambodia and Thailand is also included. A key for the Indian species is given. Images of adults and male genitalia of the new species are provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:304647E3-D409-4939-9AE3-4101EFB15FFE